Isu Impementasi Wide Area Network pada Perusahaan BUMN Manufaktur Energi - Ikhwan Rustanto (INFORMAL: Informatics Journal, 2017)
One of the companies that implement a WAN is a state-owned company manufacturing electrical energy that has one central office unit in Surabaya. State-owned company manufacturing electrical energy began to implement a WAN in 1998, the adoption of WAN been arguing their ERP implementation decision server in the central office so that the necessary WAN to access ERP applications from each unit. WAN technologies are applied in the company is Metro E (Metro Ethernet). This study will aim to evaluate the implementation of WAN technology in a manufacturing company of electrical energy supplier in Indonesia. The informants came from the headquarters unit Surabaya manufacturing company of electrical energy by doing qualitative analysis to explore the implementation results in the enterprise WAN. It is hoped this research will get what and how to use Metro E (Metro Ethernet) in WAN implementations can help the company's performance, particularly in accelerating the traffic data and company information